Long-term effects of prism adaptation in chronic visual neglect: A single case study. - Humphreys, G; Watelet, A; Riddoch, M (2006)
We investigated the effects of long-term training using prism adaptation on a patient with chronic neglect. A positive effect of prism adaptation was apparent on tests of visuo-spatial processing (cancellation, bisection, and grasping), but there was no benefit for neglect on the detection of errors on the contralesional side of words or on the detection the left side of chimeric faces. Across training sessions, the benefit of adaptation on immediate performance decreased, but it increased across sessions and within sessions when performance was tested up to 90 minutes after adaptation. The beneficial effect was maintained up to 1 year posttraining. In later sessions there were also increased negative after-effects following prism adaptation, as training progressed. There was no improvement on tests of mathematical cognition, which comprised an independent deficit in this patient. The data suggest that prolonged prism training can induce long-term adaptive spatial realignment of visuo-motor mappings, ameliorating some aspects of neglect. We discuss the implications for the rehabilitation of neglect and for understanding the neglect syndrome more generally.